How reliable and accurate is the shade determination of premolars by spectrophotometry? - Klotz, Anna-Luisa; Habibi, Yasamin; Hassel, Alexander J.; Rammelsberg, Peter; Zenthöfer, Andreas (Clinical oral investigations, 2020)
To evaluate the reliability and accuracy of spectrophotometric shade determination of premolars and to compare the results with those for incisors.